Molecular characterization of HLA class II binding to the LAG‐3 T cell co‐inhibitory receptor. Issue 2 (9th October 2020) - MacLachlan, Bruce J.; Mason, Georgina H.; Greenshields‐Watson, Alexander; Triebel, Frederic; Gallimore, Awen; Cole, David K.; Godkin, Andrew
Abstract: Immune checkpoint inhibitors (antibodies that block the T cell co‐inhibitory receptors PD‐1/PD‐L1 or CTLA‐4) have revolutionized the treatment of some forms of cancer. Importantly, combination approaches using drugs that target both pathways have been shown to boost the efficacy of such treatments. Subsequently, several other T cell inhibitory receptors have been identified for the development of novel immune checkpoint inhibitors. Included in this list is the co‐inhibitory receptor lymphocyte activation gene‐3 (LAG‐3), which is upregulated on T cells extracted from tumor sites that have suppressive or exhausted phenotypes. However, the molecular rules that govern the function of LAG‐3 are still not understood. Using surface plasmon resonance combined with a novel bead‐based assay (AlphaScreen TM ), we demonstrate that LAG‐3 can directly and specifically interact with intact human leukocyte antigen class II (HLA‐II) heterodimers. Unlike the homologue CD4, which has an immeasurably weak affinity using these biophysical approaches, LAG‐3 binds with low micromolar affinity. We further validated the interaction at the cell surface by staining LAG‐3 + cells with pHLA‐II‐multimers. These data provide new insights into the mechanism by which LAG‐3 initiates T cell inhibition. Abstract : We demonstrate that human LAG‐3 binds directly to peptide‐human leukocyte antigen class II complex (pHLA‐II) with low micromolar affinity. These findings provide new insights into the mechanism by which LAG‐3 initiates T cell inhibition and has implication for the development of novel immune checkpoint inhibitors for cancer immunotherapy.